Figure 2 from: Norarfan AF, Azreena Mokti SS, Taha H, Amin M, Ali M, Arai T (2021) DNA barcoding of a tropical anguillid eel, Anguilla bicolor (Actinopterygii: Anguilliformes), in Indo-Pacific region and notes on its population structure. Zoologia 38: 1-7. https://doi.org/10.3897/zoologia.38.e59332 - Norarfan, Ahmad Fathi; Azreena Mokti, Siti Shazwani; Taha, Hussein; Amin, Muhamad; Ali, Muhamad; Arai, Takaomi (Zenodo, 2021)
Figure 2 Maximum Parsimony tree using the COI gene sequences of Anguilla bicolor bicolor and Anguilla bicolor pacifica and additional sequences obtained from the GenBank database with indicated accession numbers. Anguilla megastoma was used as outgroup. The consistency index is 0.73, the retention index is 0.93, and the composite index is 0.82 for all sites and 0.68 for parsimony-informative sites. The percentages of the bootstrap test for Maximum Parsimony/Neighbour Joining/Maximum Likelihood are shown next to the branches.